(a) x - 1 = 0

⇒ x - 1 + 1 = 0 +1 [Adding 1 both sides]

⇒ x = 1

(b) x + 1 = 0

⇒ x + 1 - 1 = 0 -1 [Subtracting 1 both sides]

⇒ x = -1

(c) x - 1 = 5

⇒ x - 1 + 1 = 5 +1 [Adding 1 both sides]

⇒ x = 6

(d) x + 6 = 2

⇒ x + 6 - 6 = 2 - 6 [Subtracting 6 both sides]

⇒ x = -4

(e) y - 4 = -7

⇒ y - 4 + 4 = - 7 + 4 [Adding 4 both sides] ⇒ y = -3

(f) y - 4 = 4

⇒ y - 4 + 4 = 4 + 4 [Adding 4 both sides]

⇒ y = 8

(g) y + 4 = 4

⇒ y + 4 - 4 = 4 - 4 [Subtracting 4 both sides] ⇒ y = 0

(h) y + 4 = -4

⇒ y + 4 - 4 = - 4 - 4 [Subtracting 4 both sides] ⇒ y - -8